The name of Alisher Navoi is with us forever. (Questions of studying and teaching the work of Navoi) - Turakulova Okila Amirkulovna (International Consortium of Education and Culture Research Studies, 2019)
This article discusses the role of Alisher Navoi in Turkish literature, his views on the younger generation from the works of the great thinker, some issues related to the study of works of Navoi in the educational process.